Konsep Takdir dalam Cerpen Berjudul Gus Jakfar Karya Ahmad Mustofa Bisri - Saputro, Andre Rifki Aji; Suroso, Eko (UM Purwokerto Press, 2024)
One ongoing discussion that continues to be explored is the matter of destiny. This study stems from the relationship between literary works and the background of the author, which cannot be separated. The discussion focuses on the debate between two destiny doctrines regarding heaven and hell, as depicted in a short story titled